Molecular cloning of integrated Gardner-Rasheed feline sarcoma virus: genetic structure of its cell-derived sequence differs from that of other tyrosine kinase-coding onc genes. - Naharro, G (1983)
Gardner-Rasheed feline sarcoma virus (GR-FeSV) is an acute transforming retrovirus which encodes a gag-onc polyprotein possessing an associated tyrosine kinase activity. The integrated form of this virus, isolated in the Charon 21A strain of bacteriophage lambda, demonstrated an ability to transform NIH/3T3 cells at high efficiency upon transfection. Foci induced by GR-FeSV DNA contained rescuable sarcoma virus and expressed GR-P70, the major GR-FeSV translational product. The localization of long-terminal repeats within the DNA clone made it possible to establish the length of the GR-FeSV provirus as 4.6 kilobase pairs. The analysis of heteroduplexes formed between lambda feline leukemia virus (FeLV) and lambda GR-FeSV DNAs revealed the presence of a 1,700-base-pair FeLV unrelated segment, designated v-fgr, within the GR-FeSV genome. The size of this region was sufficient to encode a protein of approximately 68,000 daltons and was localized immediately downstream of the FeLV gag gene coding sequences present in GR-FeSV. Thus, it is likely that this 1.7-kilobase-pair stretch encodes the onc moiety of GR-P70. Utilizing probes representing v-fgr, we detected homologous sequences in the DNAs of diverse vertebrate species, implying that v-fgr originated from a well-conserved cellular gene. The number of cellular DNA fragments hybridized by v-fgr-derived probes indicated either that proto-fgr is distributed over a very large region of cellular DNA or represents a family of related genes. By molecular hybridization, v-fgr was not directly related to the onc genes of other known retroviruses having associated tyrosine kinase activity.